Trends in sensorimotor research and countermeasures for exploration-class space flights - Shelhamer, Mark (Frontiers in Systems Neuroscience, 2015)
Research in the area of sensorimotor and neurovestibular function has played an important role in enabling human space flight. This role, however, is changing. One of the key aspects of sensorimotor function relevant to this role will build on its widespread connections with other physiological and psychological systems in the body. The firm knowledge base in this area can provide a strong platform to explore these interactions, which can also provide for the development of effective and efficient countermeasures to the deleterious effects of space flight.